ANALISIS WAKTU TUNGGU PADA PELAYANAN UNIT LABORATORIUM RUMAH SAKIT IBU DAN ANAK SWASTA X KOTA JAKARTA - Fidyanti Shabrina Junjungsari; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2018)
The waiting time at laboratory services is still often a problem in some hospitals and has an impact on the quality of the hospital. Patients at Jakarta City X Private Owned Women and Children Hospital complained about the length of the waiting time in laboratory service, especially during peak hours. Achievements of the laboratory waiting time indicator still do not meet the standards set by the Jakarta City X Private Owned Women and Children Hospital. This purpose of this study is to describe and identify the factors that lead to long periods of waiting time in laboratory service. This research is a quantitative research and qualitative research. The data of this research were collected with an observation sheet of waiting time and with an in-depth interviews with 6 informants.The result of this research indicating that average waiting time of laboratory service is 64.11 minutes and the biggest delay is in the process of taking laboratory results. The waiting time for laboratory service that do not reach the waiting time standard is 56.7% on hospital quality indicators standard. The factors that lead this longer waiting period are the lacking numbers of employee, the layout and the space of the room that has not been optimal, and there are still standard operating procedure (SPO) that are not used as guidelines for work. The few suggestion for this case are increasing the number of employees, make effective supervision of the implementation of the SPO, and improve the layout of the laboratory room.